Pengaruh Motivasi Intrinsik dan Motivasi Ekstrinsik terhadap Kepuasan Kerja - Aditya Kamajaya Putra; Agus Frianto (BISMA (Bisnis dan Manajemen), 2018)
Human resources is one of the elements that determine the success of an organization's goals. To achieve the goals of the organization then needs to be done is to give intrinsic motivation and extrinsic motivation. Referring to doing intrinsic motivation and extrinsic motivation then will result job satisfaction. The purpose of this research is to know condition and influence intrinsic motivation and extrinsic motivation on job satisfaction employee Human Resource Department in PT. Semen Gresik (Persero) Tbk. either through partial and simultant. Samples taken by 31 respondents with a saturated sample technique. Instrument of analysis used is validity, reliability test and multiple linear regression analysis with SPSS 17 software. The results of research showed that the condition of intrinsic motivation, extrinsic motivation and job satisfaction top rated by employee Human Resource Department in PT. Semen Gresik (Persero) Tbk. Intrinsic motivation and extrinsic motivation have strong influence on job satisfaction employee Human Resource Department in PT. Semen Gresik (Persero) Tbk. either through partial and simultant